Survival Analysis of Local Political Dynasties: A Cox Proportional Hazards Model of Incumbency in Post-Decentralization Indonesia - Muhammad Hasan; Dian Rahayu; Henrietta Noir (HM Publisher, 2025)
The proliferation of political dynasties following Indonesia’s rapid decentralization has precipitated significant scholarly debate regarding democratic consolidation. While existing literature establishes the prevalence of kinship politics, few studies empirically model the temporal durability of these regimes using time-to-event analysis. This study employs a Cox Proportional Hazards Model to analyze the survival rates of 1,024 district heads (bupatis and mayors) across three electoral waves from 2005 to 2024. Data were compiled from the General Elections Commission and the World Bank INDO-DAPOER database, integrating electoral returns, fiscal capacity, and verified kinship ties. Kaplan-Meier estimates and multivariate Cox regressions were utilized to calculate Hazard Ratios for political exit. The analysis reveals that dynastic incumbents possess a significantly lower hazard of political exit compared to non-dynastic counterparts (Hazard Ratio = 0.68; p < 0.01). Fiscal autonomy acts as a critical moderator; dynasties in regions with high own-source revenue exhibit extended survival times, indicating the effective capture of local patronage networks. Conversely, corruption scandals serve as the primary accelerant of regime collapse. In conclusion, local dynasties in Indonesia utilize decentralized fiscal structures to insulate themselves from electoral competition, suggesting that high local fiscal autonomy inadvertently entrenches familial rule.